2011
DOI: 10.1038/cddis.2011.113
|View full text |Cite
|
Sign up to set email alerts
|

Labdane diterpenes protect against anoxia/reperfusion injury in cardiomyocytes: involvement of AKT activation

Abstract: Several labdane diterpenes exert anti-inflammatory and cytoprotective actions; therefore, we have investigated whether these molecules protect cardiomyocytes in an anoxia/reperfusion (A/R) model, establishing the molecular mechanisms involved in the process. The cardioprotective activity of three diterpenes (T1, T2 and T3) was studied in the H9c2 cell line and in isolated rat cardiomyocyte subjected to A/R injury. In both cases, treatment with diterpenes T1 and T2 protected from A/R-induced apoptosis, as deduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…We have recently reported that several diterpenes exert anti-inflammatory and cytoprotective actions [15][16][17]. In particular, labdane diterpenes exerted cardioprotective effects against ischemia/reperfusion (I/R)-induced injury in isolated cardiomyocytes and the mechanisms involved activation of specific survival signals and inhibition of death pathways [16]. In the present study we show a remarkable cardioprotective effect of diterpene 1 (DT1) in rat models of I/R when administered at reperfusion.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…We have recently reported that several diterpenes exert anti-inflammatory and cytoprotective actions [15][16][17]. In particular, labdane diterpenes exerted cardioprotective effects against ischemia/reperfusion (I/R)-induced injury in isolated cardiomyocytes and the mechanisms involved activation of specific survival signals and inhibition of death pathways [16]. In the present study we show a remarkable cardioprotective effect of diterpene 1 (DT1) in rat models of I/R when administered at reperfusion.…”
Section: Introductionmentioning
confidence: 53%
“…The hearts were removed and mounted on a Langendorff-perfusion apparatus as previously described [16]. Briefly, the ascending aorta was cannulated and a retrograde perfusion was maintained at a constant flow with different Ca 2+ -free Tyrode solutions.…”
Section: Global Ischemia/reperfusion (I/r) In Langendorff-perfused Ramentioning
confidence: 99%
See 3 more Smart Citations